Neonatology oxidative status in preterm infants with premature preterm rupture of membranes and fetal inflammatuar response syndrome - Elif Özalkaya; Güner Karatekin; Sevilay Topçuoğlu; Hande Özgün Karatepe; Taner Hafızoğlu; Pervin Baran; Fahri Ovalı (Elsevier, 2017)
The aim of this study, to determine an index of oxidative stress index in preterm infants less than 34 weeks gestational age with premature preterm rupture of membrane (PPROM) and fetal inflammatory response syndrome (FIRS). Methods: This study was designed as a prospective study. Fifty-one premature infants less than 35 weeks of gestational age were included in the study. The umbilical cord blood concentrations of IL-6, TAC (total antioxidant capacity) and PON-1 (paraoxonase-1) levels and TOS (total oxidative stress) were studied. The oxidative stress index (OSI = TAC/TOS) was calculated in all of prematüre infants. PPROM was defined as rupture of membranes at least 24 hours before the onset of labor. FIRS was defined by an umbilical cord IL-6 level greater than 11 pg/mL. Premature infants included in the study were divided into 4 groups. Group 1 included preterm infants without FIRS and with PPROM (n = 16), while Group 2 included preterm infants without PPROM and with FIRS (n = 9), Group 3 consisted of premature infants with PPROM and FIRS (n = 21) and Group 4 included premature infants without PPROM or FIRS (n = 5). Results: Umbilical cord TOS level was found to be higher in the preterm infants without FIRS and with PPROM (36.1 μmol H2O2 Equiv./L) compared to the preterm infants without PPROM or FIRS (11.9 μmol H2O2 Equiv./L) (p = 0.03). Umbilical cord PON-1 level was found to be lower in the preterms without FIRS and with PPROM (32 U/L), preterms without PPROM and with FIRS (30. 3 U/L) and the preterm infants with both PPROM and FIRS (48.6 U/L) compared to the preterm infants having no PPROM or FIRS (85.6 U/L) (p = 0.001). Conclusion: High pro-oxidant capacity was found in PPROM and low antioxidant capacity in PPROM and FIRS.